FRI0036 Increased macrophage infiltration and trap activity characterize subchondral bone sclerosis in knee osteoarthritis. (23rd January 2014) - Geurts, J.; Patel, A.; Helmrich, U.; Fischer, J.; Hirschmann, M. T.; Müller-Gerbl, M.; Valderrabano, V.; Hügle, T.
Abstract : Background: Recent investigations have provided substantial evidence that distinct molecular and morphological changes in subchondral bone tissue, most notably sclerosis, play an active and important role in the pathogenesis of OA. The cellular and molecular regulation of this pathological process remains poorly understood. Objectives: We investigated whether osteoimmunology, the reciprocal signaling between cells from the immune and bone system, is involved in OA subchondral bone sclerosis. Methods: Tibial plateaus and informed consent were obtained from patients undergoing total knee arthroplasty due to end-stage OA. Subchondral bone mineralization distribution was analyzed using computed tomography osteoabsoptiometry (CT-OAM) and standardized cryosections of low (non-sclerotic) and high (sclerotic) bone mineralization were prepared ( n =18 each). Cartilage degeneration was graded in Safranin- O -stained sections using the Mankin scoring system. The presence of T-lymphocytes, B-cells and macrophages was assessed using immunohistochemical staining of their respective surface markers CD3, CD20 and CD68. Osteoclast activity was visualized by staining of the enzyme marker tartrate-resistant acid phosphatase (TRAP). Cellular characterization of ex vivo subchondral bone outgrowth cultures was performed using alkaline phosphatase (ALP), TRAP staining. Correlation between histological parameters was assessed using Spearman´s rank correlation. Statistical differences were calculated using Wilcoxon signed rank test or paired t -test, where appropriate. Results: CT-OAM revealed a heterogeneous distribution of subchondral bone mineralization in OA tibial plateaus, displaying focal areas of sclerosis that overlapped macroscopically with areas of cartilage damage. These data were confirmed at the histological level by a strong correlation between Mankin score and grade of sclerosis ( r =0.7, p <0.001). Immunohistochemistry showed that CD20 +, but not CD3 +, lymphocytes and CD68 + mononuclear (macrophage) and multinucleated (osteoclast) cells were present in subchondral marrow spaces. Notably, the number of CD20 + lymphocytes and CD68 + cells was significantly ( p <0.05) increased in sclerotic subchondral bone. Enhanced osteoclast activity was confirmed by a significantly increased ( p <0.05) number of multinucleated and mononuclear TRAP + cells in sclerotic bone. Finally, the number of CD68 + cells was strongly correlated ( p <0.001) with Mankin score ( r =0.7), grade of sclerosis ( r =0.8), CD20 + lymphocytes ( r =0.8), and TRAP-positive cells ( r =0.9). Outgrowth cultures of subchondral bone showed cells of different morphologies including fibroblast-shaped osteoblasts and macrophage-like cells. Expression of ALP was detected in the prior, while TRAP expression was evident in the latter. Corresponding with histological analyses, the number of TRAP + cells was increased in ex vivo outgrowth cultures of sclerotic compared to non-sclerotic subchondral bone. Conclusions: Together, our data suggest that osteoimmunological mechanisms, specifically the interaction of CD68 + macrophages with bone-resident cells, play a - previously unknown - role in regulating subchondral bone sclerosis in progressive OA. Targeting osteoimmunology might hold potential as a disease-modifying treatment for OA. Disclosure of Interest: None Declared